Monitoring concrete structures using smart sensors - See, Dawn Hui Yun (Nanyang Technological University, 2023)
Finishing work is a common procedure found in the construction industry. It is a time consuimg and labour intensive work which requires experienced workers to carry out the job. In order to ease the finishing work for the workers, we are going to research on two different EIM systems that are to be used to monitor the hardening process of the concrete and implement it into a wireless system. In this research paper, we will be carrying out tests to determine if the two different EIM device known as the digilent and the sciospce system when used to measure the smart aggregate (SMA) if a similar result can be produced. The data collected from the two system will be recorded under the results and analysis. We will then determine which system is more suitable to be used to implement the wireless sytstem to monitor the hydration of the concrete